Safety measures during operation of biogas plant - Skliar, Oleksandr; Скляр, Олександр Григорович; Скляр, Александр Григорьевич; Boltianska, Natalia; Болтянська, Наталя Іванівна; Болтянская, Наталья Ивановна; Serebryakova, N. (НУБіП України, 2021)
TN : The rules are designed for workers who perform production tasks for the maintenance of biogas plants (BGP) during operation, as well as establish the basic requirements for maintenance of BGP [1]. General safety requirements.
Keywords: оccupational safety; medical examination; emission of toxic gases; increased noise level; vibrations; increased gas pressure